Biphasic Effects of α-Asarone on Immobility in the Tail Suspension Test: Evidence for the Involvement of the Noradrenergic and Serotonergic Systems in Its Antidepressant-Like Activity - Chellian, Ranjithkumar; Pandy, Vijayapandi; Mohamed, Zahurin (Frontiers in Pharmacology, 2016)
Alpha (α)-asarone is one of the main psychoactive compounds, present in Acorus species. Evidence suggests that the α-asarone possess an antidepressant-like activity in mice. However, the exact dose-dependent effect of α-asarone and mechanism(s) involved in the antidepressant-like activity are not clear. The present study aimed to investigate the dose-dependent effect of α-asarone and the underlining mechanism(s) involved in the antidepressant-like activity of α-asarone in the mouse model of tail suspension test (TST). In this study, the acute effect of α-asarone per se at different doses (10-100 mg/kg, i.p.) on immobility in the TST was studied. Additionally, the possible mechanism(s) involved in the antidepressant-like effect of α-asarone was studied using its interaction with noradrenergic and serotonergic neuromodulators in the TST. The present results reveal that the acute treatment of α-asarone elicited biphasic responses on immobility such that the duration of the immobility time is significantly reduced at lower doses (15 and 20 mg/kg, i.p.) but increased at higher doses (50 and 100 mg/kg, i.p.) in the TST. Besides, α-asarone at higher doses (50 and 100 mg/kg, i.p.) significantly decreased the spontaneous locomotor activity. Moreover, pretreatment of mice with noradrenergic neuromodulators such as AMPT (100 mg/kg, i.p., a catecholamine synthesis inhibitor), prazosin (1 mg/kg, i.p., an α1-adrenoceptor antagonist), yohimbine (1 mg/kg, i.p., an α2-adrenoceptor antagonist) and with serotonergic neuromodulators such as PCPA (100 mg/kg, i.p., once daily for 4 consecutive days, a serotonin synthesis inhibitor,) and WAY100635 (0.1 mg/kg, s.c., a selective 5-HT1A receptor antagonist) significantly reversed the anti-immobility effect of α-asarone (20mg/kg, i.p.). Taken together, our results suggest that the acute treatment with α-asarone elicited biphasic actions in the TST in which antidepressant-like effect was seen at relatively lower doses (15 and 20 mg/kg, i.p.) and depressive-like activity at relatively higher doses (50 and 100 mg/kg, i.p.). Furthermore, it has been revealed that the antidepressant-like effect of α-asarone could be mediated through both noradrenergic (α1 and α2 adrenoceptors) and serotonergic (particularly, 5-HT1A receptors) systems.